ANALISIS KESALAHAN SISWA DALAM MENYELESAIKAN SOAL CERITA MATEMATIKA BERDASARKAN TAHAPAN NEWMAN : SYSTEMATIC LITERATUR REVIEW - Patricia Novelina Purba, Putri; Arfriani Sihite, Mega; Efendi Hutagalung, Erwin; Muhammadin AL Fath, Ayatullah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze students’ errors in solving mathematical word problems based on Newman’s error analysis through a Systematic Literature Review (SLR) approach. Mathematics learning, particularly in word problems, requires not only computational skills but also the ability to understand, interpret, and transform problems into mathematical models. However, many students still experience difficulties, which are reflected in various types of errors. This study employed a systematic literature review method by collecting articles published between 2022 and 2026 using relevant keywords from Google Scholar. From 1,190 identified articles, 25 were selected, and 10 articles were finally analyzed in depth. The results show that students’ errors occur across all Newman stages, namely reading, comprehension, transformation, process skills, and encoding. The most dominant error is encoding error (45.50%), followed by process skills error (40.76%), comprehension error (34.70%), and transformation error (28.30%), while reading error is the lowest (12.65%). These findings indicate that students’ main difficulties lie not in reading the problems but in the problem-solving process and presenting final answers. The errors are influenced by limited conceptual understanding, lack of accuracy, and insufficient practice in expressing final conclusions. Therefore, improving mathematical literacy, conceptual understanding, and structured problem-solving skills is essential to minimize students’ errors in solving word problems.